Study on surface properties of gilt-bronze artifacts, after Nd:YAG laser cleaning - Lee, Hyeyoun; Cho, Namchul; Lee, Jongmyoung (Applied surface science, 2013)
•Corrosion products of copper onto gilt-bronze were removed by Nd:YAG laser at certain laser parameters.•Chemical cleaning did not uniformly remove copper corrosion products and separated the gold layer from the metal substrate.•Some damaged areas and brown residues on the surfaces after laser cleaning of gilt-bronze.•Brown residues were copper corrosion products mixed with soil left within the gilt layer.•Due to surface morphology of uneven and rough gilt layer, they did not react effectively to laser beams, and thus, remained as residues. As numerous pores are formed at plating gilt-bronze artifacts, the metal underlying the gold is corroded and corrosion products are formed on layer of gold. Through this study, the surfaces of gilt-bronze are being investigated before and after the laser irradiation to remove corrosion products of copper by using Nd:YAG laser. For gilt-bronze specimens, laser and chemical cleaning were performed, and thereafter, surface analysis with SEM-EDS, AFM, and XPS were used to determine the surface characteristics. Experimental results show that chemical cleaning removes corrosion products of copper through dissolution but it was not removed uniformly and separated the metal substrate and the gold layer. Nevertheless, through laser cleaning, some of the corrosions were removed with some damaged areas due to certain conditions and brown residues remained. Brown residues were copper corrosion products mixed with soil left within the gilt layer. It was due to surface morphology of uneven and rough gilt layer. Hence, they did not react effectively to laser beams, and thus, remained as residues. The surface properties of gilt-bronze should be thoroughly investigated with various surface analyses to succeed in laser cleaning without damages or residues.